Aspirin Eugenol Ester Attenuates Paraquat-Induced Hepatotoxicity by Inhibiting Oxidative Stress - Zhang, Zhen-Dong; Huang, Mei-Zhou; Yang, Ya-Jun; Liu, Xi-Wang; Qin, Zhe; Li, Shi-Hong; Li, Jian-Yong (Frontiers in Physiology, 2020)
Aspirin eugenol ester (AEE) is a new potential drug with anti-inflammatory and antioxidant stress pharmacological activity. Paraquat (PQ) is an effective and commercially important herbicide that is widely used worldwide. However, paraquat is highly toxic and can cause various complications and acute organ damage, such as liver, kidney and lung damage. The purpose of this study was to investigate whether AEE has a protective effect on hepatotoxicity induced by PQ in vivo and in vitro. Cell viability, apoptosis rate, mitochondrial function and intracellular oxidative stress were detected to evaluate the protective effect of AEE on PQ-induced BRL-3A (normal rat hepatocytes) cytotoxicity in vitro. In vivo, AEE pretreatment could attenuate oxidative stress and histopathological changes in rat liver induced by PQ. The results showed that AEE could reduce the hepatotoxicity induced by PQ in vivo and in vitro. AEE may reduce PQ-induced hepatotoxicity by inhibiting oxidative stress and maintaining mitochondrial function. This study proved that AEE is an effective antioxidant and can reduce the hepatotoxicity of PQ.